Bildungssprachliche Mittel Eine Analyse von Schülertexten aus dem Sachunterricht der Primarstufe - Fornol, Sarah L. (Empirische Forschung im Elementar- und Primarbereich, 2020)
The aim of the present study is to identify educational language devices that primary school pupils produce within non-fiction texts and to examine them with regard to their form-function relationship within non-fiction texts. The study is based on 474 texts written by learners in the second to fourth grades. In order to correspond to the complexity of the object of research, all 474 texts were first examined for the realisation of educational language devices by means of a cross-method triangulation with sequential design with the help of a quantitative frequency analysis on the basis of a deductively developed category system. Subsequently, a partial corpus (n=28) of the data material was selected by means of interleaved sampling and a content-structuring qualitative content analysis was carried out on the basis of a deductively-inductively developed category system in order to relate the educational language devices back to their function. The results of the study complement the findings of previous studies and provide important indications for future research into the means and skills of the language of education. At the same time, the findings enable conclusions to be drawn for the design of language-sensitive subject teaching.